Biochemical, colour and sensory attributes of pasteurized sugarcane juice stored in high‐density polyethylene‐based nanocomposite films. Issue 6 (1st March 2022) - Manikantan, M. R.; Pandiselvam, R.; Arumuganathan, T.; Khanashyam, Anandu Chandra; Varadharaju, N.
Abstract: The shelf life of the sugarcane juice ('Mandya' variety Co 62175), packed in high‐density polyethylene‐based nanocomposite films, was investigated for 60 days with 15 different combinations and thickness of nanoclay and compatibilizer. To assess the product's stability, physicochemical, microbiological and sensory tests were performed at 15‐day intervals. The bio‐chemical quality attributes, namely, total sugars, pH, total soluble solids and overall acceptability scores, were found to decline with regard to storage period under ambient conditions. The pH, total soluble solids (TSS) and total sugar content varied from 5.18–4.83, 19.20–18.10°Brix and 18.21–17.54 g/100, respectively. The microbial quality of the stored juice was found to be depended on the quantity of compatibilizer, nanoclay and thickness of the packaging film. Among the developed nanocomposite high‐density polyethylene (HDPE) films, material E (with 2% and 5% of nanoclay and compatibilizer, with 100‐μm thickness) and material G (with 6% and 5% of nanoclay and compatibilizer, with 100‐μm thickness) showed better physiochemical stability with zero microbial population in the sugarcane juice. Abstract : The high‐density polyethylene‐based nanocomposite films have a great potential for packaging and preservation of fruit juices and beverages.